PENGEMBANGAN SOP PELAYANAN ADMINISTRASI PEMERINTAHAN KAMPUNG BERBASIS TEKNOLOGI INFORMASI DI KAMPUNG INOFI - Rijal Rijal; Djamil Hasim; Irwan Irwan; Djunaedi Djunaedi; Jusman Jusman (Jurnal Abdimas Bina Bangsa, 2023)
Development of Standard Operating Procedures (SOP) for government administration services in Inofi Village, Biak Numfor Regency, by utilizing information technology, the aim of which is to increase the efficiency and effectiveness of village government administration services, as well as utilizing the potential of information technology in this process. The process of government administration services in Inofi Village still experiences several obstacles, such as the lack of use of information technology, procedures that are not yet properly standardized, and a lack of training for administrative officers. Therefore, it is necessary to socialize the development of SOPs for information technology-based government administration services. The proposed SOP will include clear steps in the administrative service process, including the use of information technology to support the process. In addition, there will be recommendations for training administrative officers in using the necessary information technology. By implementing the administrative service SOP that has been developed, it is hoped that it can increase the efficiency and effectiveness of government administration services in Inofi Village. The use of information technology is also expected to facilitate access to information for village communities and increase transparency in government processes